2020
DOI: 10.3390/nu12010194
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Metabolic and Mental Health of Children with Obesity: A School-Based Nutrition Education and Physical Activity Intervention in Wuhan, China

Abstract: This study aimed to evaluate the effectiveness of a school-based nutrition education and physical activity intervention on cardiovascular risk profile and mental health outcomes among Chinese children with obesity. Two primary schools were randomly allocated to the control group (CG) and the intervention group (IG). We selected children with obesity from 1340 students in the third and fourth grades as participants. The IG received 8 months of nutrition education and physical activity intervention, while the CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…With the new, less strict eligibility criteria, n = 28 studies were found, which met the inclusion criteria, from which n = 12 were included in the meta-analysis (Figure 1B). Two of these were RCTs, which were also included in part 1 (Jazaieri et al, 2012;Yu et al, 2020). The other two RCTs (Hartmann et al, 2010;Lokös et al, 2013) could not be included because the relevant data were not reported.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the new, less strict eligibility criteria, n = 28 studies were found, which met the inclusion criteria, from which n = 12 were included in the meta-analysis (Figure 1B). Two of these were RCTs, which were also included in part 1 (Jazaieri et al, 2012;Yu et al, 2020). The other two RCTs (Hartmann et al, 2010;Lokös et al, 2013) could not be included because the relevant data were not reported.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
“…Furthermore, the control interventions were not comparable between the studies (CBT, MBSR, no treatment, usual practice with no intervention). Only one RCT (Yu et al, 2020) reported a power analysis, and therefore, we cannot decide if the sample sizes were overall large enough to be able to detect a difference in the main outcome of the effect of PA on SAD between the different groups.…”
Section: Interim Discussion Part 1 (Randomized Controlled Trials)mentioning
confidence: 99%
See 3 more Smart Citations